Peran Brand Appeal dan Brand Differentiation Terhadap Personal Branding Mahasiswa Generasi Z - Rommy Mochamad Ramdhani; Brillian Rosy; Dwi Nova Wijaya; Dewi Fitrotus Sa'diyah; Eva Mufidah; Budiana Ruslan (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to analyze the influence of Brand Appeal and Brand Differentiation on Personal Branding among Generation Z students who actively use social media to build their digital portfolios. A quantitative approach with a survey method was employed. The research population consisted of students from the Office Administration Education Study Program, Universitas Negeri Surabaya. Samples were taken using purposive sampling with 259 respondents, and data were collected through an online questionnaire (Google Form). The analysis technique used PLS-SEM with SmartPLS 3. The results show that both variables have important contributions to the formation of personal branding in the digital environment. Theoretically, this study extends the application of Self Determination Theory (SDT) in the context of personal branding in the digital era. The findings indicate that the basic psychological needs in SDT namely autonomy, competence, and relatedness are reflected in individual behavior when building a digital identity through brand appeal and brand differentiation. Practically, this study provides implications for Generation Z in developing effective personal branding strategies on social media.